Sales Performance of Khadi and Village Industries Products in Pudukottai District – Sarvodaya Sanghs - Dr.P.S. Nagarajan, K. Murugan (International Journal of Advanced Science and Technology, 2019)
Micro, Small and Medium Enterprises (MSME) is being the heart of Indian economy and employment. It is extremely heterogeneous in the mode of the nature of the industry, size of the enterprises and several of product and service and also the technologies which undertakes therein. The developing country like India, the contribution of MSME is highly inevitable. It provides a platform for innovative, effective and efficient entrepreneurial spirit. It reduces regional imbalances and also assuring equitable distribution of national income and wealth through industrialization of rural and backward areas. The MSME have come across many reengineering practices as of now. This study aimed to analyse the effect of reengineering practices attempted on MSMEs. Keyword:. MSME, Entrepreneurship, Simple Seasonal Time series Analysis, Paired Sample t-test, Employment